Skin CD4+ Memory T Cells Play an Essential Role in Acquired Anti-Tick Immunity through Interleukin-3-Mediated Basophil Recruitment to Tick-Feeding Sites - Ohta, Takuya; Yoshikawa, Soichiro; Tabakawa, Yuya; Yamaji, Kayoko; Ishiwata, Kenji; Shitara, Hiroshi; Taya, Choji; Oh-hora, Masatsugu; Kawano, Yohei; Miyake, Kensuke; Yamanishi, Yoshinori; Yonekawa, Hiromichi; et al. (Frontiers in Immunology, 2017)
Ticks, blood-sucking arthropods, serve as vectors for transmission of infectious diseases including Lyme borreliosis. After tick infestation, several animal species can develop resistance to subsequent infestations, reducing the risk of transmission. In a mouse model, basophils reportedly infiltrate tick-feeding sites during the second but not first infestation and play a crucial role in the expression of acquired tick resistance. However, the mechanism underlying basophil recruitment to the second tick-feeding site remains ill-defined. Here, we investigated cells and their products responsible for the basophil recruitment. Little or no basophil infiltration was detected in T-cell-deficient mice, and adoptive transfer of CD4+ but not CD8+ T cells reconstituted it. Il3 gene expression was highly upregulated at the second tick-feeding site, and adoptive transfer of interleukin-3 (IL-3)-sufficient but not IL-3-deficient CD4+ T cells conferred the basophil infiltration on T-cell-deficient mice, indicating that the CD4+ T-cell-derived IL-3 is essential for the basophil recruitment. Notably, IL-3+ resident CD4+ memory T cells were detected even before the second infestation in previously uninfested skin distant from the first tick-feeding site. Taken together, IL-3 produced locally by skin CD4+ memory T cells appears to play a crucial role in basophil recruitment to the second tick-feeding site.